Nanocarriers for effective delivery of benznidazole and nifurtimox in the treatment of chagas disease: A review - Arrua, Eva Carolina (2019)
Neglected tropical diseases (NTDs) constitute a group of infectious diseases prevalent in countries with tropical and subtropical climate that affect the poorest individuals and produce high chronic disability associated with serious problems for the health system and socioeconomic development. Chagas disease or American trypanosomiasis is included on the NTDs list. However, even though this disease affects more than 10 million people, mostly in Latin America, causing the death of over 10,000 people every year, only two drugs are approved for its treatment, benznidazole and nifurtimox. These antiparasitic agents were developed almost half a century ago and present several biopharmaceutical disadvantages such as low aqueous solubility and permeability limiting their bioavailability. In addition, both therapeutic agents are available only as tablets and a liquid pediatric formulation is still lacking. Therefore, novel pharmaceutical strategies to optimize the pharmacotherapy of Chagas disease are urgently required. In this regard, nanotechnological approaches may be a crucial alternative for the delivery of both drugs ensuring an effective pharmacotherapy although the successful bench-to-bedside translation remains a major challenge. The present work reviews in detail the formulation and in-vitro/in-vivo analysis of different nanoformulations of nifurtimox and benznidazole in order to enhance their solubility, dissolution, bioavailability and trypanocidal activity.